Reducing Water and Energy Consumption in Urban Communities by Treating Gray Wastewater with Photoelectrocatalytic Method - Mohammad Negahban; Abdoreza Karbassi (آب و فاضلاب, 2023)
Urban wastewater combines black and gray wastewater, which can be thought of as a way to separate and optimize its treatment. In this research, the separation and recycling of gray water treated by photoelectrocatalytic method, to be used in irrigation of plants, etc., has been investigated. First, the gray wastewater of a 10-unit residential building was sampled. BOD and COD concentrations were measured by respirometry and closed reflux calorimetry, respectively. Then, the removal efficiency of photoelectrocatalytic treatment by direct current with titanium and graphite electrodes, at two current densities of 10 and 20 mA/cm2 and at three electrode distances of 6, 12 and 15 cm, and the feasibility of using this method from the point of view of energy consumption, was studied. Based on the results, the optimal conditions for pollutant removal have been obtained at a current density of 20 mA/cm2 and a distance of 12 cm between the electrodes in a period of 60 minutes. With an increase in current density, the removal efficiency increases and as the distance between the electrodes increases, the removal efficiency experiences an increase with partial changes, but, it causes an elevation in voltage, resulting in an augmented consumption of electrical energy. The initial pH decreased with increasing voltage and further decreased with decreasing electrode distance. The amount of electrical energy consumed in the photoelectrocatalytic reactor is estimated to be about 2 kWh/m3 and 11.43 kilowatts per kilogram of COD removal. The results indicate a 64% reduction in water consumption at the site of operation, a reduction in energy consumption in the water and wastewater distribution and treatment system, and as a result, a reduction in CO2 production. Although the possibility of using the photoelectrocatalytic system on a large scale requires more studies, other suitable methods can be used.